Islamization of the Malay Worldview: Sufi Metaphysical Writings - Moris, Megawati (IDOSI, 2011)
In his seminal essay, Preliminary Statement on a General Theory of the Islamization of the Malay-Indonesian Archipelago, Syed Naquib al-Attas stated that “Islam came to the Archipelago couched in Şūfī metaphysics.” According to him, Malay intellectual history began with the Islamization of the worldview of the Malays which was primarily effectuated by Malay Sufi scholars. They accomplished this through oral transmission and written works of their teachings in Malay on the intellectual aspects of Islam and especially on metaphysics. The first metaphysical writings in Malay appeared during the sixteenth century in Aceh and they marked the beginning of not only a wider transmission of Islamic teachings but a more profound or ‘intensified’ understanding of the religion as well. This process of Islamization of the Malay worldview as propounded by al-Attas continued even after the seventeenth century which marked its third and last phase in which fundamental concepts related to the Islamic worldview continued to be expounded, defined and clarified. To attest to his theory that it was through Sufi metaphysics basically that the Malay worldview was Islamized, in this paper I have chosen to present and discuss an example of writing on metaphysics written in Malay during the eighteenth century by ‘Abd al-Şamad al-Palimbānī. In a section of his book entitled Siyar al-sālikīn ilā ‘ibādat Rabb al-‘ālamīn (Ways of the spiritual travelers to the Lord of the worlds) ‘Abd al-Şamad wrote to examine and clarify on an Islamic conception of the nature of Being and Reality for the benefit of his Malay readers.